Estimation of measurement uncertainty for determination of sulphate content in cement by an alternative approach - Završnik, Lina (RMZ-materials and geoenvironment, 2016)
The precise and accurate determination of sulphate levels in cement is of utmost importance due to the potential occurrence of internal sulphate attack in concrete, which affects the latter%s durability, and thus, also the safety of concrete constructions. The estimated measurement uncertainty provides a level of confidence in the experimental results, and enables the comparison of data, both between different laboratories and between different methods. This paper presents an alternative approach to the estimation of measurement uncertainty in the determination of sulphate in cement, based on the use of proficiency testing data. The calculations used in this procedure refer to the estimation of reproducibility within-laboratory component of the analysis of control samples, as well as of the bias component of sulphate content data for different types of Portland cement derived from several proficiency testing trials.
Keywords: cement; sulfat; sulphate; measurement uncertainty; merilna negotovost; alternative approach; alternativni pristop